Assessment of the Overall and Multidrug-Resistant Organism Bioburden on Environmental Surfaces in Healthcare Facilities. (13th September 2016) - Shams, Alicia M.; Rose, Laura J.; Edwards, Jonathan R.; Cali, Salvatore; Harris, Anthony D.; Jacob, Jesse T.; LaFae, Anna; Pineles, Lisa L.; Thom, Kerri A.; McDonald, L. Clifford; Arduino, Matthew J.; Noble-Wang, Judith A.
Abstract : OBJECTIVE: To determine the typical microbial bioburden (overall bacterial and multidrug-resistant organisms [MDROs]) on high-touch healthcare environmental surfaces after routine or terminal cleaning. DESIGN: Prospective 2.5-year microbiological survey of large surface areas (>1, 000 cm 2 ). SETTING: MDRO contact-precaution rooms from 9 acute-care hospitals and 2 long-term care facilities in 4 states. PARTICIPANTS: Samples from 166 rooms (113 routine cleaned and 53 terminal cleaned rooms). METHODS: Using a standard sponge-wipe sampling protocol, 2 composite samples were collected from each room; a third sample was collected from each Clostridium difficile room. Composite 1 included the TV remote, telephone, call button, and bed rails. Composite 2 included the room door handle, IV pole, and overbed table. Composite 3 included toileting surfaces. Total bacteria and MDROs (ie, methicillin-resistant Staphylococcus aureus, vancomycin-resistant enterococci [VRE], Acinetobacter baumannii, Klebsiella pneumoniae, and C. difficile ) were quantified, confirmed, and tested for drug resistance. RESULTS: The mean microbial bioburden and range from routine cleaned room composites were higher (2, 700 colony-forming units [CFU]/100 cm 2 ; ≤1–130, 000 CFU/100 cm 2 ) than from terminal cleaned room composites (353 CFU/100 cm 2 ; ≤1–4, 300 CFU/100 cm 2 ). MDROs were recovered from 34% of routine cleaned room composites (range ≤1–13, 000 CFU/100 cm 2 ) and 17% of terminal cleaned room composites (≤1–524 CFU/100 cm 2 ). MDROs were recovered from 40% of rooms; VRE was the most common (19%). CONCLUSIONS: This multicenter bioburden summary provides a first step to determining microbial bioburden on healthcare surfaces, which may help provide a basis for developing standards to evaluate cleaning and disinfection as well as a framework for studies using an evidentiary hierarchy for environmental infection control. Infect Control Hosp Epidemiol 2016;1426–1432